Efficient Conversion of Glucose into Lactic Acid over the Lewis Acidity Enhanced Sn-Beta Catalyst - Fenfen Guo; Yuxuan Wang; Zhicheng Jiang; Youjing Tu; Ruikai Li; Xingyu Zhang; Aoyi Tang; Yuan Liang; Lishi Yan; Hu Luo; Shenggang Li; Lingzhao Kong (Molecules)
The catalytic production of lactic acid from carbohydrates was considered a green way to efficiently utilize renewable biomass resources. In this study, an easy post-synthesis method was used to prepare a Sn-Beta catalyst for the production of lactic acid from glucose at 180 °C, 2 MPa, and 30 min. With optimized reaction time, temperature, pressure, and the ratio of raw material to catalyst, the yield of lactic acid reached an astonishingly high level of 76.0%. In addition, the catalyst characterizations were performed in-depth, revealing the intrinsic relationship between catalyst performance and structure, proving that the 2 wt% Sn was uniformly dispersed in the skeleton of Beta zeolite, which significantly increased the density of Lewis acid. Thus, the enhanced isomerization and retro-aldol condensation processes over the Lewis acid sites led to the high yield of lactic acid. This catalytic system kept stable after five cycles at mild conditions, showing high potential for industrial biomass utilization.